Multiparametric Early Detection and Prediction of Cardiotoxicity Using Myocardial Strain, T1 and T2 Mapping, and Biochemical Markers: A Longitudinal Cardiac Resonance Imaging Study During 2 Years of Follow-Up. (16th June 2021) - Giusca, Sorin; Korosoglou, Grigorios; Montenbruck, Moritz; Geršak, Blaž; Schwarz, Arne Kristian; Esch, Sebastian; Kelle, Sebastian; Wülfing, Pia; Dent, Susan; Lenihan, Daniel; Steen, Henning
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Our goal was to evaluate the ability of cardiovascular magnetic resonance for detecting and predicting cardiac dysfunction in patients receiving cancer therapy. Left ventricular ejection fraction, global and regional strain utilizing fast-strain-encoded, T1 and T2 mapping, and cardiac biomarkers (troponin and BNP [brain natriuretic peptide]) were analyzed. Methods: Sixty-one patients (47 with breast cancer, 11 with non-Hodgkin lymphoma, and 3 with Hodgkin lymphoma) underwent cardiovascular magnetic resonance scans at baseline and at regular intervals during 2 years of follow-up. The percentage of all left ventricular myocardial segments with strain ≤−17% (normal myocardium [%]) was analyzed. Clinical cardiotoxicity (CTX) and sub-CTX were defined according to standard measures. Results: Nine (15%) patients developed CTX, 26 (43%) had sub-CTX. Of the 35 patients with CTX or sub-CTX, 24 (69%) were treated with cardioprotective medications and showed recovery of cardiac function. The amount of normal myocardium (%) exhibited markedly higher accuracy for the detection of CTX and sub-CTX compared with left ventricular ejection fraction, T1, and T2 mapping as well as troponin I (Δareas under the curve=0.20, 0.24, and 0.46 for normal myocardium (%) versus left ventricular ejection fraction, troponin I, and T1 mapping, P <0.001 for all). In addition, normal myocardium (%) at baseline accurately identified patients with subsequent CTX ( P <0.001), which was not achieved by any other markers. Conclusions: Normal myocardium (%) derived by fast-strain-encoded cardiovascular magnetic resonance, is an accurate and sensitive tool that can establish cardiac safety in patients with cancer undergoing cardiotoxic chemotherapy not only for the early detection but also for the prediction of those at risk of developing CTX. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT03543228.